Evaluation of Flexural Behavior of Prestressed Concrete (PSC) Hollow-Core Slabs (HCSs) - Dong-Hwan Kim; Min-Jun Kim; Min-Su Jo; Hyeong-Gook Kim; Yeo-Jin Yoon; Kil-Hee Kim (Buildings, 2023)
This study aimed to evaluate the flexural behavior characteristics of prestressed concrete hollow-core slabs (HCSs) through bending experiments. Six specimens were used as variables, both with and without reinforced concrete, in the HCS. A four-point load was applied in the form of a simple support beam to assess the flexural behavior and ultimate strength of HCS. The results demonstrate that, compared to non-reinforced specimens, the reinforced HCS exhibited higher maximum loads and better ductility performance. The experimental outcomes demonstrate that HCS showed an average of 10% higher capacity than the maximum load of the concrete structure standards (KDS 14 20 20, ACI 318-19, and PCI handbook), with or without reinforced concrete, leading to relatively safe predictions. This study’s experimental findings are anticipated to aid in evaluating structural safety in a relatively secure way. The findings indicate that the HCS structural system is excellent at sustaining the weight of a structure and ensuring its safety. Additionally, this investigation is anticipated to furnish practical guidance for optimizing the use of HCS systems in structural design and construction.